2020
DOI: 10.3390/molecules25245945
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Immobilized Battacin Lipopeptide Gels with Activity against Bacterial Biofilms

Abstract: Novel antibiotic treatments are in increasing demand to tackle life-threatening infections from bacterial pathogens. In this study, we report the use of a potent battacin lipopeptide as an antimicrobial gel to inhibit planktonic and mature biofilms of S. aureus and P. aeruginosa. The antimicrobial gels were made by covalently linking the N-terminal cysteine containing lipopeptide (GZ3.163) onto the polyethylene glycol polymer matrix and initiating gelation using thiol-ene click chemistry. The gels were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It can be clearly seen that the biofilm on the silicone sheet in the NPs-treated group was more severely damaged, the adhesions and number of the bacteria were significantly decreased, the area of the biofilm was reduced, and the three-dimensional structure was obviously destroyed and cleared, demonstrating the excellent biofilm elimination ability of the CD-CS-BA-NPs. According to the in vitro biofilm elimination experiments, the elimination was quantified by crystal violet staining due to it is able to bind to the exopolysaccharide matrix in the biofilm, 50 the decrease of OD value indicated that the integrity of the biofilm was destroyed, which were matching with the observations made from SEM. On the other hand, the number of colonies on the silicone sheet in the NPs-treated group was significantly decreased compared with the BA solution-treated group and the model group ( Figure 7 ), indicating that BA may exhibit a better bactericidal ability in vivo when CD-CS-BA-NPs were employed for drug delivery, which is generally consistent with the results of MIC determination and the pathological tissue section observations.…”
Section: Resultsmentioning
confidence: 68%
“…It can be clearly seen that the biofilm on the silicone sheet in the NPs-treated group was more severely damaged, the adhesions and number of the bacteria were significantly decreased, the area of the biofilm was reduced, and the three-dimensional structure was obviously destroyed and cleared, demonstrating the excellent biofilm elimination ability of the CD-CS-BA-NPs. According to the in vitro biofilm elimination experiments, the elimination was quantified by crystal violet staining due to it is able to bind to the exopolysaccharide matrix in the biofilm, 50 the decrease of OD value indicated that the integrity of the biofilm was destroyed, which were matching with the observations made from SEM. On the other hand, the number of colonies on the silicone sheet in the NPs-treated group was significantly decreased compared with the BA solution-treated group and the model group ( Figure 7 ), indicating that BA may exhibit a better bactericidal ability in vivo when CD-CS-BA-NPs were employed for drug delivery, which is generally consistent with the results of MIC determination and the pathological tissue section observations.…”
Section: Resultsmentioning
confidence: 68%
“…Several lipopeptides have demonstrated antimicrobial activity against S. aureus , as is the case of the antibiotic daptomycin used to treat severe Gram-positive infections, the first molecule of this class to reach commercial application 24 . Lipopeptides have also demonstrated anti-biofilm activity 56 , 57 and anti-quorum sensing effects 17 against S. aureus . Fengycin produced by a probiotic Bacillus inhibited the quorum sensing system of S. aureus and prevented its colonization in the human intestine 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the reported hydrogels lack antibacterial properties, leading to the proliferation of bacteria around the mucosa ( Figure 11 ). 100
Figure 11 The Schematic diagram of antimicrobial lipopeptide gel formation in methanol through covalent photo polymerization under UV irradiation. Reproduced with permission from De Zoysa GH, Wang K, Lu J, et al Covalently immobilized battacin lipopeptide gels with activity against bacterial biofilms.
…”
Section: Biomedical Applications Of Pda Hydrogel In Oral Tissuesmentioning
confidence: 99%